PATHOGENESIS OF CARDIOVASCULAR COMPLICATIONS IN DIABETIC PATIENTS: A COMPREHENSIVE ANALYSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Diabetes mellitus poses a major global health burden, with cardiovascular complications being the primary cause of illness and death. This study explores the key pathogenic mechanisms linking diabetes to cardiovascular damage, including glucose toxicity, oxidative stress, inflammation, and endothelial dysfunction. Hyperglycemia triggers metabolic disturbances, mitochondrial impairment, and vascular remodeling, while advanced glycation end products, reactive oxygen species, and cytokine activation lead to myocardial injury and atherosclerosis. Understanding these mechanisms is vital for developing effective therapeutic strategies and improving cardiovascular outcomes in diabetic patients.